tBRD-1 Selectively Controls Gene Activity in the Drosophila Testis and Interacts with Two New Members of the Bromodomain and Extra-Terminal (BET) Family. - Theofel, I.; Bartkuhn, M.; Hundertmark, T.; Boettger, T.; Gärtner, S.M.; Leser, K.; Awe, S.; Schipper, M.; Renkawitz-Pohl, R.; Rathke, C. (PLoS ONE, 2014)
Multicellular organisms have evolved specialized mechanisms to control transcription in a spatial and temporal manner. Gene activation is tightly linked to histone acetylation on lysine residues that can be recognized by bromodomains. Previously, the testis-specifically expressed bromodomain protein tBRD-1 was identified in Drosophila. Expression of tBRD-1 is restricted to highly transcriptionally active primary spermatocytes. tBRD-1 is essential for male fertility and proposed to act as a co-factor of testis-specific TATA box binding protein-associated factors (tTAFs) for testis-specific transcription. Here, we performed microarray analyses to compare the transcriptomes of tbrd-1 mutant testes and wild-type testes. Our data confirmed that tBRD-1 controls gene activity in male germ cells. Additionally, comparing the transcriptomes of tbrd-1 and tTAF mutant testes revealed a subset of common target genes. We also characterized two new members of the bromodomain and extra-terminal (BET) family, tBRD-2 and tBRD-3. In contrast to other members of the BET family in animals, both possess only a single bromodomain, a characteristic feature of plant BET family members. Immunohistology techniques not only revealed that tBRD-2 and tBRD-3 partially co-localize with tBRD-1 and tTAFs in primary spermatocytes, but also that their proper subcellular distribution was impaired in tbrd-1 and tTAF mutant testes. Treating cultured male germ cells with inhibitors showed that localization of tBRD-2 and tBRD-3 depends on the acetylation status within primary spermatocytes. Yeast two-hybrid assays and co-immunoprecipitations using fly testes protein extracts demonstrated that tBRD-1 is able to form homodimers as well as heterodimers with tBRD-2, tBRD-3, and tTAFs. These data reveal for the first time the existence of single bromodomain BET proteins in animals, as well as evidence for a complex containing tBRDs and tTAFs that regulates transcription of a subset of genes with relevance for spermiogenesis.